Educational aims of rights education in primary school – zooming in on teachers and pupils in two classes. Issue 5 (3rd July 2020) - Quennerstedt, Ann
ABSTRACT: The role of education in upholding and spreading human rights is widely recognised, but knowledge about actual rights education is limited. Drawing on north European didaktik theory, this article examines human rights teaching and learning of 8–9-year-old pupils in two Swedish classes, with a special interest in what teachers and pupils consider to be the aim of rights education – what is to be achieved? Based on interviews with teachers and children and observed teaching and classwork, a shared conception between teachers and pupils focusing on knowledge about rights and ethical allegiance with rights is identified, but also some differences.